Evidence of aerosol transmission of African swine fever virus between two piggeries under field conditions: a case study - Li, Xiaowen; Hu, Zhiqiang; Fan, Mingyu; Tian, Xiaogang; Wu, Weisheng; Gao, Wenchao; Bian, Lujie; Jiang, Xiaoxue (Frontiers in Veterinary Science, 2023)
African swine fever (ASF) is a devastating and economically significant infectious disease and has caused huge losses in the commercial pig sector in China since 2018. The major transmission route of African swine fever virus (ASFV), the causative agent of ASF, is direct pig-to-pig contact or indirect contact with virus-contaminated objects. Although aerosol transmission route of ASFV has been reported under experimental conditions previously, whereas no reports described under field conditions. In this case study, aerosol-associated samples were collected in the monitoring period of 24 days in an ASFV-positive farm. A complete and clear chain of ASFV transmission route by aerosols was observed: pigs in Room A-aerosol in Room A-dust of air outlets in Room A-outdoor aerosols-dust of air inlets in Room B-aerosols/pigs in Room B. And fluorescent powder experiment proved dust transmission from Room A to Room B. This is the first report to provide evidence of aerosol transmission route of ASFV under field conditions, and further research is needed to study aerosol-transmission laws of ASFV and develop effective strategies for air filtration or air disinfection to create low-risk fresh air for pig herds.